Colloidal TiO2-Modified Mesoporous Electron Transport Layer in Perovskite Solar Cells - Yustiani, Evira Bella; Anggraini, Putri Nur; Shobih, Shobih; Widianto, Eri; Retnaningsih, Lilis; Soepriyanto, Syoni; Santoso, Imam; Nursam, Natalita Maulani (National Research and Innovation Agency, 2023)
The electron transport layer (ETL) is a crucial part in perovskite solar cells (PSC) as it specifically governs the charge extraction at the perovskite/ETL interface. In this study, methylammonium lead iodide-based PSCs with an n-i-p structure were fabricated and modified by adding colloidal TiO2 into the mesoporous TiO2 film as ETL. The effect of the colloidal TiO2 addition on the PSC performance was investigated for ETL comprising different types of TiO2 particles, i.e. P25 and anatase TiO2. Despite producing lower performance than the PSC made with commercial paste, the power conversion efficiency of the PSCs could be improved with the introduction of colloidal TiO2 solution. An optimum condition was observed depending on the type of TiO2 particle, where the best performing device was achieved with colloidal TiO2 of 0.4 and 0.2 mL for P25 and anatase TiO2, respectively. The amount of colloidal TiO2 in samples with P25 overall had less impact than the samples with anatase TiO2.